Pengaruh Stres Akademik dan Manajemen Waktu Terhadap Prokrastinasi Akademik Mahasiswa Fakultas Psikologi UHAMKA - Putri, Regitha Ananda; Andriany, Anissa Rizky (Jurnal Ilmiah Penelitian Psikologi, 2023)
Abstract Procrastination is the behavior of getting rid of activities or tasks that should be completed immediately. In the world of lectures, some students tend to do activities they like and leave things they don't like, such as academic affairs, so that the tasks to be completed end up piling up. The tendency to procrastinate is due to various factors such as time management problems or academic stress experienced by students. Academic stress is a response that is raised by individuals when they cannot meet academic demands. While time management is a person's ability to organize themselves in dealing with time by making a priority scale so that it is organized. This study aims to determine the effect of academic stress and time management on academic procrastination of UHAMKA psychology faculty students. This study uses a quantitative approach. Respondents in this study were 54 active psychology students selected using a purposive sampling technique. The time management measurement tool used the Time Management Behavior Scale (TMBS) with Cronbach alpha 0.883, academic stress used the Academic Stress Inventory (ASI) scale with Cronbach alpha 0.922 and procrastination used the Tuckman Procrastination Scale with Cronbach alpha 0.716. The collected data were analyzed by using multiple linear regression analysis with the SPSS v.26 application. The results showed that the R value was 0.679 and the R Squere was 0.460, with a probability value of 0.000 (P<0.001). This means that there is a significant effect of academic stress and time management on academic procrastination, with the contribution of time management and academic stress on academic procrastination in students of the Faculty of Psychology, University of Muhammadiyah Prof. Dr. Hamka by 46.0 percent. Furthermore, the results of the study of the academic stress variable obtained a value of β = -0.021 with a probability value of 0.861 (p> 0.05) for academic procrastination. This means that there is no effect of academic stress on academic procrastination. While the time management variable has a value of β = -0.689 and has a probability value of 0.000 (p <0.001) for academic procrastination. It can be interpreted that there is an influence of time management on academic procrastination. The better one's time management, the lower the academic procrastination. Keywords: academic; academic stress; academic procastination; student; time management.